2015
DOI: 10.1016/j.gheart.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Presentation, Diagnosis, and Management of Acute Coronary Syndromes: Findings From the Kerala-India ACS Registry

Abstract: Background Previous literature from high-income countries has repeatedly shown sex differences in the presentation, diagnosis, and management of acute coronary syndromes (ACS), with women having atypical presentations and undergoing less aggressive diagnostic and therapeutic measures. However, much less data exist evaluating sex differences in ACS in India. Objectives This study sought to evaluate sex differences in the diagnosis, management, and treatment of patients with ACS in Kerala, India. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 21 publications
0
26
1
Order By: Relevance
“…However, we have previously demonstrated similar treatment and in-hospital clinical outcomes between men and women in Kerala, including death, reinfarction, stroke, heart failure, or cardiogenic shock, after adjustment for baseline differences in comorbidities and presentation. 10 Individuals allocated to the ACS QUIK quality improvement intervention group had higher quality of life scores. We have previously demonstrated higher treatment rates, including reperfusion and anti-angina medications at discharge, in the intervention group compared with the control group.…”
Section: Discussionmentioning
confidence: 96%
“…However, we have previously demonstrated similar treatment and in-hospital clinical outcomes between men and women in Kerala, including death, reinfarction, stroke, heart failure, or cardiogenic shock, after adjustment for baseline differences in comorbidities and presentation. 10 Individuals allocated to the ACS QUIK quality improvement intervention group had higher quality of life scores. We have previously demonstrated higher treatment rates, including reperfusion and anti-angina medications at discharge, in the intervention group compared with the control group.…”
Section: Discussionmentioning
confidence: 96%
“…lower incomes and education) are more vulnerable than those with higher socio-economic status [9][10][11][12]. While some evidence suggests that acute coronary outcomes may not vary significantly by sex in India [13], a greater burden of risk factor among males has been observed globally and in Indian studies as well [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In its initial report, the registry found that ST-elevation myocardial infarction (STEMI) was the most common presentation (37%), followed by non-ST elevation myocardial infarction (NSTEMI) (31%) and unstable angina (32%; P < 0.001 for difference between the groups). 14 A higher proportion of patients with unstable angina had a history of prior diabetes compared with patients who presented with STEMI and non-STEMI (40.7% in unstable angina vs. 37.9% in NSTEMI vs. 34.6% in STEMI), stroke (3.2% vs. 2.2% vs. 2.2%), and percutaneous coronary intervention or coronary artery bypass graft surgery (PCI or CABG) (0.7% vs. 0.1% vs. 0.1%; P < 0.001 for all). On the other hand, history of prior hypertension (40.4% in unstable angina vs. 48.2% in NSTEMI vs. 55.5% in STEMI) and smoking (30.2% vs. 37.9% vs. 35.3%; P < 0.001 for all) was more prevalent among STEMI and non-STEMI patients.…”
Section: Secondary Prevention After Myocardial Infarctionmentioning
confidence: 99%
“… High rate of missing data. Kerala Acute Coronary Syndrome registry 13 , 14 2013 Patients presenting to the hospital with acute coronary syndrome (ACS). n = 25,748 Observed in-hospital mortality for ACS patients was around 8%.…”
Section: Introductionmentioning
confidence: 99%